Rubber band engineer : build slingshot-powered rockets, rubber band rifles, unconventional catapults and more guerilla gadgets from household hardware /: build slingshot-powered rockets, rubber band rifles, unconventional catapults and more guerilla gadgets from household hardware. (2016) - Akiyama, Lance
No abstract available